Farmers’ Income and the Driving Forces for the Switch from Shifting Cultivation to Settled Agriculture in Meghalaya, India - Mebaaibok L Nonglait; Nicholas Khundrakpam; Pratibha Deka (Universitas Sebelas Maret, 2024)
This study assesses the dependence of farmers on semi-settled (a combination of shifting and settled cultivation) and settled agriculture as a source of family income. The farmers residing in the hilly tracts of West Garo Hills mostly adopt semi-settled cultivation. Farmers are also transitioning from semi-settled to settled agriculture. This study was conducted to investigate the factors influencing the transition and the socioeconomic conditions of farmers practicing semi-settled and settled agriculture. The researchers surveyed 119 randomly selected households in West Garo Hills, a district of Meghalaya, India, using a structured questionnaire. Exploration of influencing factors for transitioning is important to provide insights into how factors interact, thereby facilitating the development of effective adaptation strategies and policies that will ensure farmers’ future well-being. Results showed that settled farmers generate more income and possess more land area than semi-settled farmers. Besides available land area, a stable source of income for a family is a strong determinant for abandoning shifting cultivation and transitioning to settled agriculture to boost income with less time investment and labor. The farmers found that shifting cultivation helped meet their dietary needs and some income during the COVID-19 lockdown. Alongside efforts to boost commercial agriculture, the government should also assist farmers with limited resources in transitioning to settled agriculture by building market networks for the goods produced from shifting cultivation.